Lost Economic Potential Caused by Stunting in Kudus Regency: Evaluation of Socialization of Activities for Calculating Lost Economic Potential with the Konig Method - Sayuti; Heru Sulistyo; Mulyana; Aleknaek Martua (Civitas Consecratio: Journal of Community Service and Empowerment, 2025)
The United Nations' Sustainable Development Goals (SDGs) have several points that are relevant to the issue of stunting, particularly those related to health and well-being. Stunting can have an impact on society, affecting the economy, education, and social development. In the context of government, stunting has a negative economic impact and therefore needs to be reduced. The Kudus Regency Government is currently making efforts to reduce stunting rates and aims to achieve zero percent by 2024. Stunting is one of the most critical issues that need to be addressed by the current regent and the next elected regent. The purpose of this community service activity is to provide technical guidance on calculating the economic losses caused by stunting. The method used to calculate the economic losses caused by stunting is the Konig method. Estimating the economic losses caused by stunting is necessary to serve as the basis for allocating funds to stunting programs in Kudus Regency. In the initial presentation phase, the preliminary analysis revealed that 98% of respondents were unaware of the economic potential lost due to stunting. During the activity, the team presented materials to explain the methods used to analyze the economic potential lost due to the impact of stunting in Kudus Regency. The final results of the analysis show that stunting in Kudus Regency causes an economic loss of 627.97 billion rupiah every year. The final evaluation results indicate that 100% of respondents assessed that the presentation of the material provided knowledge in reducing stunting rates in Kudus Regency. Academic recommendations for policymakers are expected to provide empirical evidence of the economic losses as a basis for the need for effective activities to reduce stunting rates in Kudus Regency. With this, stunting rates can be further reduced, and it is hoped that the economic losses caused by stunting in the following years can be minimized.